Validity and reliability of a new device (WIMU®) for measuring hamstring muscle extensibility - Muyor, J. M. (International Journal of Sports Medicine, 2017)
The aims of the current study were 1) to evaluate the validity of the WIMU® system for measuring hamstring muscle extensibility in the passive straight leg raise (PSLR) test using an inclinometer for the criterion and 2) to determine the test-retest reliability of the WIMU® system to measure hamstring muscle extensibility during the PSLR test. 55 subjects were evaluated on 2 separate occasions. Data from a Unilever inclinometer and WIMU® system were collected simultaneously. Intraclass correlation coefficients (ICCs) for the validity were very high (0.983-1); a very low systematic bias (-0.21°--0.42°), random error (0.05°-0.04°) and standard error of the estimate (0.43°-0.34°) were observed (left-right leg, respectively) between the 2 devices (inclinometer and the WIMU® system). The R2 between the devices was 0.999 (p<0.001) in both the left and right legs. The test-retest reliability of the WIMU® system was excellent, with ICCs ranging from 0.972-0.995, low coefficients of variation (0.01%), and a low standard error of the estimate (0.19-0.31°). The WIMU® system showed strong concurrent validity and excellent test-retest reliability for the evaluation of hamstring muscle extensibility in the PSLR test.